Complications after cytoreductive surgery with hyperthermic intraperitoneal chemotherapy for treatment of peritoneal carcinomatosis: Risk factors for ICU admission and morbidity prognostic score. (March 2016) - Malfroy, Sylvain; Wallet, Florent; Maucort-Boulch, Delphine; Chardonnal, Laurent; Sens, Nicolas; Friggeri, Arnaud; Passot, Guillaume; Glehen, Olivier; Piriou, Vincent
Abstract: Background and objectives: For patients suffering from peritoneal carcinomatosis, cytoreductive surgery and Hyperthermic Intraperitoneal Chemotherapy (HIPEC) is the only curative option. We focused on severe complications in the postoperative course of HIPEC. Methods: We studied perioperative data from patients who underwent HIPEC between January 2010 and August 2011. Our primary objective was to identify perioperative risk factors for ICU admission. Our secondary objective was to identify patient that may be re-admitted to the ICU thanks to a prognostic score. Results: 122 patients underwent HIPEC. 32 presented severe adverse events (26.2%) and 7 died (5.7%). Reasons for ICU admission were septic shock in 28.1% of patients, hemorrhagic shock for 21.9%, hemodynamic instability for 15.6%, respiratory causes for 6.2% and post-operative acidosis for 6.2%. Vasopressors were required for 34% and 40.6% were mechanically ventilated. Conclusion: Peritoneal cancer index, diaphragmatic peritonectomy, the need of vasopressive therapy, total volume of fluid leakage collected in drains and total volume of fluid therapy administered at day 1 reported on ideal body weight were the 5 significant variables that we combined to build a morbidity prognostic score. One patient over 4 is likely to present severe complications. A predictive morbidity score provide informative data for clinicians.